Niveles de riesgo en las mujeres víctimas de violencia intrafamiliar del barrio Isidro Ayora alto del cantón Loja - Montaño Tejedor, Emérita Beatriz (2019)
The present thesis research entitled "Levels of risk in women victims of domestic violence in the Isidro Ayora neighborhood of the Loja canton" allowed to fulfill the general objective that was established as "Determine the levels of risk that occur in cases of intrafamily violence in the women of the Isidro Ayora neighborhood of the city of Loja, to contribute with a social action plan aimed at the prevention of violence. " The methodologies used during the research process showed its efficiency, pertinence and feasibility, it was the Scientific Method, supported by its auxiliary methods such as: the Inductive, Deductive, Analytical and Synthetic method, which allowed to have direct contact with women of the neighborhood to have a clear vision of the object of study, in addition, obtain relevant information that served to know and detail the research problem. The techniques used were: The survey applied to 20 women, the unstructured interview applied to the president of the neighborhood, the Director of the Chonta Cruz Subcenter, the chief of police of the communal police unit of colored lands, the VIFJ4 scale (Violencia Intrafamiliar of Dr. Julio in 2014) applied to 20 women, through instruments such as questionnaire based on multiple choice questions and criteria, in order to obtain valuable information on the object of study. The results obtained, showed the main events found in the field research where it reflects, that psychological violence is the one that most affects this population studied with a level of severe risk, and who exercises violence in the home of their partner. Faced with this problem, it is considered appropriate to design a social action plan aimed at preventing violence in the homes of women in the Isidro Ayora neighborhood, which will consist of several strategic activities that enable integrated work, wherever they may be. the managers of their own change and in this way contribute to the welfare and improve the quality of life of women and get out of the cycle of violence.